2017
DOI: 10.1038/s41598-017-09000-y
|View full text |Cite
|
Sign up to set email alerts
|

The protein and mRNA expression levels of glial cell line-derived neurotrophic factor in post stroke depression and major depressive disorder

Abstract: Previous studies have indicated that the level of glial cell line-derived neurotrophic factor (GDNF) may be correlated with stroke and depression. Here, we investigated whether GDNF can be a discriminant indicator for post stroke depression (PSD). 159 participants were divided into four groups: PSD, stroke without depression (Non-PSD), major depressive disorder (MDD) and normal control (NC) group, and the protein and mRNA expression levels of GDNF in serum were measured. The results showed that only MDD group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 33 publications
0
10
0
1
Order By: Relevance
“…Higher levels are reported in mood disorders, AUD and ADHD 26 , 28 31 . Zhang et al did not find any effect of medication in GDNF levels 32 . Conversely, data from in vitro studies demonstrate increased levels of GDNF in the presence of antidepressants and mood stabilizing agents 1 , 4 , 27 .…”
Section: Discussionmentioning
confidence: 94%
“…Higher levels are reported in mood disorders, AUD and ADHD 26 , 28 31 . Zhang et al did not find any effect of medication in GDNF levels 32 . Conversely, data from in vitro studies demonstrate increased levels of GDNF in the presence of antidepressants and mood stabilizing agents 1 , 4 , 27 .…”
Section: Discussionmentioning
confidence: 94%
“…It was found that the level of protective neurotrophic GDNF in the brain of patients with MDD was related to age ( Sun et al, 2019 ). The protein and mRNA expression of GDNF decreased in patients with depression ( Zhang Y. et al, 2017 ). The level of GDNF in patients with advanced MDD was significantly decreased ( Diniz et al, 2012 ).…”
Section: The Underlying Mechanism Of Depressionmentioning
confidence: 99%
“…Increasing evidence suggests that miRNAs are involved in the process of ischemic stroke (Zhang et al, 2017). A large number of studies have used miRNA treatment to reduce ischemic brain injury and functional recovery after stroke (Volný et al, 2015;Sen, 2019;Van Kralingen et al, 2019;Yuan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%